2023
DOI: 10.1038/s42003-022-04402-9
|View full text |Cite|
|
Sign up to set email alerts
|

Single-cell transcriptomics reveal extracellular vesicles secretion with a cardiomyocyte proteostasis signature during pathological remodeling

Abstract: Aberrant Wnt activation has been reported in failing cardiomyocytes. Here we present single cell transcriptome profiling of hearts with inducible cardiomyocyte-specific Wnt activation (β-catΔex3) as well as with compensatory and failing hypertrophic remodeling. We show that functional enrichment analysis points to an involvement of extracellular vesicles (EVs) related processes in hearts of β-catΔex3 mice. A proteomic analysis of in vivo cardiac derived EVs from β-catΔex3 hearts has identified differentially e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…For example, research has shown that increased levels of CRYAB in glioblastoma patients are closely related to decreased survival rates and increased susceptibility to metastatic diseases. The expression of the CRYAB gene has been identified as a prospective diagnostic indicator for a range of cancers, including prostate cancer, colorectal cancer, and gastric cancer ( 65 ). The assessment of CRYAB gene expression levels offers valuable insights into the prognosis and treatment response of various tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research has shown that increased levels of CRYAB in glioblastoma patients are closely related to decreased survival rates and increased susceptibility to metastatic diseases. The expression of the CRYAB gene has been identified as a prospective diagnostic indicator for a range of cancers, including prostate cancer, colorectal cancer, and gastric cancer ( 65 ). The assessment of CRYAB gene expression levels offers valuable insights into the prognosis and treatment response of various tumors.…”
Section: Discussionmentioning
confidence: 99%
“…hiPSC-CMs are increasingly recognized as a relevant in vitro model to study human cardiomyocyte biology. In addiZon, these cells release EVs 12,13,15,19,[40][41][42][43][44][45][46] , although the variaZons in the heterogeneity of these EVs remain unclear. The protocol applied here 47 enabled the generaZon of a pure populaZon of beaZng cardiomyocytes (Figure S1, Video S1).…”
Section: Hipsc-derived Cardiomyocytes (Hipsc-cms) Secrete Small Extra...mentioning
confidence: 99%
“…These independent or combined "single" technologies have helped us not only to create a high-resolution SC type map of human tissues [127] and three-dimensional nuclear architecture, gene expression, and epigenetic modifications, [128] but also to assess and analyze immune cell differentiation, [129,130] to uncover cellular and molecular mechanisms and to discover new therapeutic targets for human diseases, [49,[131][132][133] in particular COVID-19 and CVDs, as well as to trace cancer progression. [134] It can be said that this is indeed a new "single" era of biomedicine and its current implications and research in both CVDs and COVID-19 [135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150] as well as others will definitely open a new beautiful future.…”
Section: Cavdmentioning
confidence: 99%